1993
DOI: 10.5014/ajot.47.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Contingent Interaction During Work and Play Tasks for Mothers With Multiple Sclerosis and Their Daughters

Abstract: Occupational therapy has focused on activity as a catalyst for understanding human roles and interactions, regardless of whether disability or chronic illness is present. Parenting is an important interactional activity accompanied by specific role expectations. This investigation examined the interaction patterns of mothers with multiple sclerosis and their daughters. Thirty-one mothers with multiple sclerosis and their daughters aged 8 to 12 years were compared with 34 mothers without disabilities and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 8 publications
0
20
0
1
Order By: Relevance
“…Of the 18 eligible studies (see Table 1), locations of study participants were as follows: United States (n = 4) [12,15,16,18], Canada (n = 3) [13,17,22], Switzerland (n = 2, 1 of which also included Germany and Greece) [8,23], Greece (n = 2) [7,21], UK (n = 1) [14], Israel (n = 2) [24,25], Australia (n = 4) [5,10,19,20]. Cohort sizes ranged from 8 [10] to 281 [12], with a total of 2051 children or adolescents studied overall.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 18 eligible studies (see Table 1), locations of study participants were as follows: United States (n = 4) [12,15,16,18], Canada (n = 3) [13,17,22], Switzerland (n = 2, 1 of which also included Germany and Greece) [8,23], Greece (n = 2) [7,21], UK (n = 1) [14], Israel (n = 2) [24,25], Australia (n = 4) [5,10,19,20]. Cohort sizes ranged from 8 [10] to 281 [12], with a total of 2051 children or adolescents studied overall.…”
Section: Resultsmentioning
confidence: 99%
“…All study participants were recruited mainly through university neurology departments or specific national or local MS society centres. MS-specific clinical information on the affected parent were noted in some studies, with 2 providing a quantitative measure of disability (based on Kurtzke’s Expanded Disability Status Scale [EDSS] [37] score), with the affected parents ranging from an EDSS of 2 to 7, indicating ‘slight weakness’ through to ‘restricted to a wheelchair’ [16,23]. A further 9 studies provided other means of quantifying impairment, again with parents ranging from minimal impairment to wheelchair bound [7,8,10,14,15,17,19-21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that mother-daughter interactions during work and play tasks were perceived as similar, irrespective of whether the mother had MS. 31 Similarly, other studies have shown that children with an MS-affected parent did not appear to differ from the community norms for overall difficulties and externalizing problems. 6,9 However, these studies showed that parents with MS were more likely to report that their children had psychological problems.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little documented information on the experience of parenting with arthritis. The emphasis of most available literature is on physical disability in general, focusing on the effect of the parent's disability on child development rather than the parenting experience per se (Crist, 1992). Studies reveal that when one member of a family is disabled, the entire family experience the disability in some way, and there is great potential for family disruption (Miller et al, 1983;Ryan et al, 1996).…”
mentioning
confidence: 99%